STUDI LAJU PERKEMBANGAN BUAH KAKAO PASCA APLIKASI MEDIA JAMUR TIRAM (Pleurotus ostreatus (Jacq) P. Kumm) - Roliana Roliana; Umrah Umrah; Miswan Miswan (Biocelebes, 2015)
The study Cocoa Fruit rate Post Application Development Media Media Mushroom Compost Waste Oyster Mushroom (Pleurotusostreatus (Jacq) P. Kumm) This study was conducted in the village Langaleso, in order to determine the effect of dose and post-application of compost media oyster mushroom (Pleurotusostreatus( Jacq) P. Kumm) on the rate of development of the fruit and seed weight of cocoa. The research was designed in completely randomized design (CRD), consisting of seven treatments and three replications. The composition of the treatment of waste compost fertilizer applications on any media oyster mushroom cocoa plant P (control, without fertilizer application), P1 (application of compost 500 g), P2 (application of compost in 1000 g), P3 (compost application 1500g), P4 (compost application 2000 g), P5 (compost application 2500 g), P6 (3000 g of cocoa compost applications). Parameter observations pace of development of the cocoa plant fruit and cocoa bean weight. The rate of development of cocoa pods showed between fruit length and circumference of fruit on a day to Fifty. Results of the study showed weight cocoa beans treated (P5) is the best treatment in terms of the average weight of the cocoa beans 45.81 g.Keywords : Cocoa Beans, Compost Waste Oyster Mushroom Media, (Pleurotus ostreatus (Jacq) P.Kumm)